Wear assessment of Cr2O3‐/TiAlN‐coated DAC‐10 tool steel against steel and Al2O3 counterbodies. Issue 3 (30th October 2021) - Kumar, Sunil; Maity, Saikat Ranjan; Patnaik, Lokeswar
Abstract: TiAlN film was deposited on Cr2 O3 ‐coated plasma‐nitrided DAC‐10 tool steel to obtained multilayer Cr2 O3 /TiAlN coating layer using cathodic arc deposition technique. The structural make‐up of the coating was characterized using Atomic Force Microscopy (AFM) and X‐ray diffraction methods, and the mechanical properties were evaluated using nanoindentation and nanoscratch test. The structural phases of the coating indicated the presence of crystalline CrO structure and cubic TiAlN phases. The coating showcased improved hardness (38 GPa), elastic modulus (387 GPa), and adhesion along with appreciable H/E (0.09) and H 3 /E 2 (0.366 GPa) attributes. Further, friction‐induced wear behavior of the coating was investigated against steel and Al2 O3 counterbodies under dry sliding conditions. The wear behavior of the coating was greatly influenced by its hardness and deformation properties and frictional behavior of the counterbodies. More spikes and fluctuation were observed in the frictional curve against Al2 O3 counterbody attributed to the emanation of TiO2, Cr2 O3, and Al2 O3 compounds due to dry sliding leading to the formation of flakes and delamination induced debris. Against the steel counterbody, the coating mainly formed a typical smooth glossy surface ascribed to the formation of Fe2 O3 compound on the worn surface.